2004
DOI: 10.1074/jbc.m406346200
|View full text |Cite
|
Sign up to set email alerts
|

Human Heme Oxygenase Oxidation of 5- and 15-Phenylhemes

Abstract: Human heme oxygenase-1 (hHO-1) catalyzes the O 2 -dependent oxidation of heme to biliverdin, CO, and free iron. Previous work indicated that electrophilic addition of the terminal oxygen of the ferric hydroperoxo complex to the ␣-meso-carbon gives 5-hydroxyheme. Earlier efforts to block this reaction with a 5-methyl substituent failed, as the reaction still gave biliverdin IX␣. Surprisingly, a 15-methyl substituent caused exclusive cleavage at the ␥-meso-rather than at the normal, unsubstituted ␣-meso-carbon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The results showed that one atom of labeled oxygen was incorporated from water and one from the peroxide or dioxygen into the corresponding para-substituted benzoic acid product, as previously reported for the oxidation of ␣-meso-phenylmesoheme (supplemental Fig. S4) (23). No oxygen-18 was incorporated into biliverdin from H 2 18 O 2 , in accord with the fact that the two lactam oxygens arise from two different molecules of O 2 (supplemental Fig.…”
Section: Oxygen-18 Incorporation Into the Products-oxygen-18supporting
confidence: 68%
See 4 more Smart Citations
“…The results showed that one atom of labeled oxygen was incorporated from water and one from the peroxide or dioxygen into the corresponding para-substituted benzoic acid product, as previously reported for the oxidation of ␣-meso-phenylmesoheme (supplemental Fig. S4) (23). No oxygen-18 was incorporated into biliverdin from H 2 18 O 2 , in accord with the fact that the two lactam oxygens arise from two different molecules of O 2 (supplemental Fig.…”
Section: Oxygen-18 Incorporation Into the Products-oxygen-18supporting
confidence: 68%
“…CO Formation Assay-Horse myoglobin (Sigma) was used as a CO trap according to the protocol previously described (23). The reactions (1 ml) consisted of 10 M arylmesoheme-hHO-1 complex, 60 nM CPR, and 100 M NADPH in standard buffer and were allowed to proceed for 20 min in a sealed container before the addition of myoglobin via syringe to a final concentration of 4 M.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations